Pengaruh Budaya Organisasi Terhadap Kinerja Aparatur Sipil Negara Di Sekretariat Dprd Kabupaten Mamuju Provinsi Sulawesi Barat - Akbar, Muhammad Akbar; Malik, Ihyani; Mustari, Nuryanti (Universitas Muhammadiyah Makassar, 2021)
This study aimed to determine the effect of Organizational Culture on the Performance of the Civil Servants in the Secretariat of the Mamuju Regency of West Sulawesi Province. This research was associative in nature by measuring the influence of Organizational Culture with the performance of Civil Servants and explaining the influence of the variables examined using quantitative research methods. The data used were primary and secondary data and the unit of analysis was the civil servants at the Mamuju Regency DPRD Secretariat. The results of the data analysis had an influence between the variable X on the variable Y From the calculation of the product moment correlation coefficient, the implementation of Organizational Culture influences the Civil Servants Performance in the Secretariat of DPRD Mamuju Regency. This was evidenced from the results of the calculation of correlation obtained t count that was equal to 7,036 and the level of relationship was high. Then from the results of these calculations it could be seen that the coefficient of determination was 42.5%